1966
DOI: 10.1128/jb.91.5.1677-1680.1966
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Wall-less Bacteria by Streptococcal and Staphylococcal Toxins

Abstract: Earlier studies demonstrating that staphylococcal a-toxin and streptolysin S have the capacity to lyse protoplasts and spheroplasts of certain species of bacteria and Mycoplasma have been extended to encompass additional kinds of wall-less bacteria including L forms. It is suggested that sensitivity to staphylococcal a-toxin and streptolysin S may be explicable in terms of specific phospholipid composition of cell membranes, whereas sensitivity to streptolysin 0 is dependent upon the presence in cell membranes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1968
1968
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…remain undefined. Preparations of stabilized SLS are lytic to bacterial protoplasts and spheroplasts (Bernheimer, 1966), but to date no definitive bacteriocidal activities against cell-wall competent bacteria have been defined in co-culture experiments comparing wild type and SLSnegative mutant GAS (Nizet et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…remain undefined. Preparations of stabilized SLS are lytic to bacterial protoplasts and spheroplasts (Bernheimer, 1966), but to date no definitive bacteriocidal activities against cell-wall competent bacteria have been defined in co-culture experiments comparing wild type and SLSnegative mutant GAS (Nizet et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that cholesterol is involved in the lytic action (2,3). Such a sterol could serve as the receptor site (or substrate) for the toxin (1). Although these toxins may be similar in many ways, the same mechanism of action may not necessarily be found for each member of this group of toxins.…”
Section: Fig 2 (A)mentioning
confidence: 99%
“…Protoplasts of Streptococcus faecalis (ATCC 9790) were prepared by the method of Shockman and Slade (61) by use of 1 mg of lysozyme per ml for 16 hr at 37 C. The protoplasts were sedimented by centrifugation and were suspended in 0.5 M sucrose in 0.05 M phosphate buffer (pH 6.6) containing 0.01 M Mga+. Micrococcus lysodeikticus protoplasts were prepared with lysozyme as reported by Bernheimer (5). Protoplasts of Bacillus megaterium KM and Sarcina lutea and spheroplasts of Escherichia coli W [prepared with lysozyme and ethylenediaminetetraacetic acid (EDTA)J and Vibrio metschnikovii were obtained as previously described (10).…”
Section: Gel Filtration Chromatography Gel Ifitration Was Performed mentioning
confidence: 99%